A harmony search-based H-infinity control method for islanded microgrid. (April 2020) - Sedhom, Bishoy E.; El-Saadawi, Magdi M.; Elhosseini, Mostafa A.; Saeed, Mohammed A.; Abd-Raboh, Elhossaini E.
Abstract: This paper proposes a harmony search (HS) based H-infinity (H ∞ ) control method to promote the conventional droop control method. The proposed method is used to enhance the performance of the voltage/frequency (V/F), controller. It can regulate both voltage and frequency to their rated values while enhancing autonomous microgrid (MG) power quality. The results gained from the proposed controller were compared with the results achieved by using the model predictive control (MPC) technique to show the applicability of the proposed controller. On top of that, a comparison between different controllers presented in this paper is performed. Highlights: Controlling the islanded MG voltage and frequency and improving its power quality. Enhancing the performance of the droop control by applying the H ∞ robust control. Proposing HS-based H ∞ control method to obtain the controller weighting parameters. Investigating the system stability and the multiplicative stability margin (MSM). Performing robustness analysis in the presence of parameters uncertainties.